Peningkatan Pembelajaran Cara Hidup Bersih dan Sehat (PHBS) dengan Penyuluhan Kesehatan Gigi dan Cuci Tangan - Ana Setyowati; Swasti Artanti; Ida Baroroh; Ivan Chabibillah (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2020)
Health status is one of the important elements in efforts to improve the Indonesian Human Development Index (HDI). Meanwhile, the degree of health is not only determined by health services, but what is more dominant is the environmental conditions and people's behavior. Efforts to change people's behavior in order to support the improvement of health status are carried out through the Clean and Healthy Behavior (PHBS) development program. The aim of community service is to provide dental health education and hand washing. The method of health education carried out is the method of preparation of activities, the stages of implementation of activities, namely (1) Socialization and Licensing, (2) Conducting Affirmations and Pre Tests (3) Conducting dental health education and hand washing. (4) Evaluate the results of health education activities with the Post Test. The results of counseling activities that there is an increase in understanding and knowledge about the importance of Clean and Healthy Behavior, especially about Dental Health and Hand Washing.